2009
DOI: 10.1139/l09-070
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between innovation and performance of construction firms

Abstract: This paper studies the performance of 118 major Korean construction companies between 1997 and 2003 to verify empirically the existence of a direct relationship between innovations of firms and their performance. This time period was selected because there had been a radical change in the market leadership of the construction industry due to the Asian Financial Crisis of the late 1990s. The AMOS analysis and the research demonstrated that innovation of a firm has an indirect relationship with its performance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Choi et al (2009) argued that a firm’s performance is a direct indication of its level of innovativeness. This was evident in the results as it was observed that firms’ efficiency and productivity targets affected their choice of innovation route.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al (2009) argued that a firm’s performance is a direct indication of its level of innovativeness. This was evident in the results as it was observed that firms’ efficiency and productivity targets affected their choice of innovation route.…”
Section: Resultsmentioning
confidence: 99%
“…It was obtained that innovation affects the efficiency of workers [108]. Innovation will ultimately boost productivity via employee generating ideas for novel services and products [108], better administrative processes, enhance efficiencies and successful job management [109], improve organization suitability [110], and increase overall organizational performance and efficiency [108]. Innovation would also improve the quality, quantity, and timeliness of production, involvement in the workplace, and efficiency to complete the task [109].…”
Section: Development Of Research Hypothesesmentioning
confidence: 99%
“…Innovation in architecture, engineering, and construction (AEC) was commonly known as construction innovation which is defined as ''apply new ideas, technologies, products or processes to solve construction problems, increase resource efficiency or improve living standards'' [13]. From the perspective of industry, construction innovation improves the productivity of the construction industry [30] and the performance and competitiveness of construction enterprises [31]. Innovation is significant to save resources, improve management efficiency, increase project reliability and enhance project sustainability [32].…”
Section: B Innovation and Sustainable Constructionmentioning
confidence: 99%